الفلسفة العربية في مائة عام، إشكاليات ومناهج وآفاق: (One Hundred Years of Arabic Philosophy: Problematics, Approaches & Prospects) - أبو يعرب المرزوقي (At-Tajdid - Intellectual Refereed Journal, 2022)
-